Rehabilitation of Post-stroke Hemiplegic Patient with Integrative Medicine - Ruangravevat, Kittiphum; Veerapattananon, Siraprapa; Noiprasert, Sulakkana; Rattanachaisit, Watchara; Hongsing, Parichart (Greater Mekong Subregion Medical Journal, 2021)
Numerous of stroke survivors are suffering from the body function impairments such as problems with balance or coordination, weakness, and paralysis. We describe a case in which use of integrative medicine rehabilitation for a 52-year-old female patient with ischemic stroke suffered a right hemiplegia, resulting in persistent weakness and problems with muscle control. The patient underwent sequential three healing processes including physical therapy, Thai traditional massage, and acupuncture in total of 10 times, at 2 times per week by professional practitioners. After management with this rehabilitation program, the patient had better effects on stroke recovery evaluating by The Barthel index for activities of daily living, Mini-Mental Status Examination (MMSE) Thai 2002 and muscle power grading. The outcomes of the study evidence that comprehensive integrative medicinal rehabilitation approach has multiple effects on individuals who have poststroke disability or weakness to confer greater rehabilitative benefit.